Sebaran Kualitas Air Teluk Pamukan - Sadar Husaini; Muhammad Ruslan; Mijani Rahman; Leila Aryani Sofya (EnviroScienteae, 2020)
Teluk Pamukan is the closest fishing ground used by fishermen who live on the coast of Teluk Pamukan. Apart from fisheries, several other activities in the Teluk Pamukan area include industrial shipping or coal transportation traffic using barges, transportation of crude palm oil (CPO), and is an area for loading and unloading fertilizers and oil palm kernels by tankers. This activity has led to allegations of disturbance in the aquatic ecosystem in the form of a decrease in water quality, particularly in fishing areas. The decrease in water quality will certainly affect the status of water quality that is no longer by its designation so that it can cause social problems in the community. The purpose of this research was to identify the general characteristics of Teluk Pamukan, map the distribution patterns of water quality and the scale of water quality in Teluk Pamukan, and to analyze fishermen's perceptions of the decline in water quality. The sampling location was in the waters of Teluk Pamukan. The method used to determine the status of water quality was the Pollutant Index according to the opinion of Sumitomo and Nemerow (1970). The results obtained can be concluded that the environmental quality scale for each parameter varied from very bad to very good. However, the results of the pollutant index calculation at all stations were included in the Moderately Polluted category